"Restrictive Conditions" in patent law and the competition law interface. (24th May 2018) - Lai, Jessica C.; Kathuria, Vikas
Abstract : This article examines a little discussed section of the New Zealand Patents Act 1953 (s 66), which dealt with "restrictive conditions." It discusses the repeal of the section and the resultant situation in New Zealand, particularly vis‐à‐vis the competition law regime and its exemptions for certain behavior regarding intellectual property. A comparison of the patent‐law and competition‐law interface is made with respect to the UK, Australia, and India. The article finds that New Zealand's statutory regime potentially offer the most patent friendly environment when it comes to a patentee's ability to extend his/her reach beyond the scope of patent rights. At the same time, policy‐ and law‐makers have largely ignored the relationship between patent law and competition law, which may prove to be counterproductive against New Zealand's desire to be innovative and—connected to this—unfavorable for New Zealand consumers.